EFFECT OF NITROGENOUS FERTILIZER SOURCES AND ANTI-TRANSPIRATION IN THE ROOT OF POTATO PLANT AND CONTENT OF THE CONCENTRATION OF NITRATE AND CYTOKININE AND PROLINE - & et al., Mageed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was conducted in experimental field, Department of Horticulture, College of Agriculture –University of Baghdad, Abo Graib for two spring seasons 2011, 2012 potatoes yield. This study  was included the effect of using of three type from nitrogen fertilizer, as well as to  comparison procedure ( Zero) Her code N0,N1,N2,N3 , and two anti- transpiration  , as well as to comparison procedure ( Zero) Her code AS0,AS1,AS2. This study was made by using the activity experiences (4*3) within   the design RCBD with three repeated. The most important results can be summarized Palate: The procedure N3AS2   have increased nitrogen rate in the roots as moral for two season as (561.6%, and 76.3 %) continuously in the first season. but the rate of prolin in the roots have marked in the procedure N3AS1in the first seasons and the procedure N3AS0 in the two seasons of study as (1.60, and 1.80 Micro. gm. /gm.)  Continuously. It excelled treatment N3AS2 in concentration by giving them cytokeinin As for the recipe dry root weight observed treatment N3AS1 moral superiority to the rest of the transaction by giving 4.06 g in the first season while the transaction marked N1AS1 moral superiority to the rest of the transaction in the second season by giving 8.78 g.